Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan Pada Bengkel Pelita Motor - Bimbing, Alfin; Tamengkel, Lucky F.; Mukuan, Danny D. S. (JURNAL ADMINISTRASI BISNIS (JAB), 2024)
This study aims to determine whether service quality affects customer satisfaction at Pelita Motor Workshop. This research is quantitative research with a simple linear regression analysis technique. The sample in this study amounted to 60 respondents. Statistical tests used in this study were validity tests, reliability tests, normality tests, simple correlation coefficient tests, partial tests, and determination tests. proved to be correct and acceptable. Through the determination test, it was found that service quality had an effect of 63,5% on customer satisfaction at Pelita Motor Workshop.